Effect of oral vanadyl sulfate treatment on serum enzymes and lipids of streptozotocin-diabetic young rats - Pepato, Maria Teresa [UNESP]; Magnani, MRT; Kettelhut, I. C.; Brunetti, Iguatemy Lourenço [UNESP] (Kluwer Academic Publ, 1999)
In this work we investigate the possible toxicity of vanadyl sulfate (VOSO4), a compound capable of reducing hyperglycemia, on the following serum enzymes of diabetic young rats: alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LD) and creatine kinase (CK), as well as its effects on serum lipids. We find that at a concentration of 1 mg/mL VOSO4 has no toxic effect on the liver and muscles of diabetics young rats. These findings suggest that VOSO4 may be an alternative to insulin in the near future, due to its low cost, low toxicity and ready availability.
Keywords: vanadyl sulfate; hyperglycemia; diabetes mellitus; insulin; serum enzymes